Kato Nan Ampek Sebagai Bentuk Representatif Komunikasi Dakwah Berbasis Kearifan Budaya Lokal Perspektifvbudaya Minangkabau - Hendra, Tomi (IAIN Padangsidimpuan, 2024)
Religion and culture are important elements and contribute to building the character of a region. Where with these two things can be an identity in social life, for example the Minangkabau culture which is known by the philosophy of Adaik Basandi Syara', Syara' Basandi Kitabullah, Adaik Mamakai, Syarak Mangato. In the element of language, Minangkabau culture has a code of ethics or manners in communication known as kato nan ampek. Through the philosophy of kato nan ampek, there are methods of communication based on Islamic values. This research aims to see the representation of da'wah communication through kato nan ampek as a representative form of local cultural wisdom from the perspective of Minangkabau culture. This research uses Library research method or Library research. Where this research is not a field study, but is done by literature review of written data. In this study, it can be seen that Minangkabau culture has representative da'wah communication in communicating in the form of kato nan ampek as a form of local wisdom of Minang culture in the perspective of da'wah communication, namely first, kato mandaki which is intended for the older, second kato manurun which is used for the smaller, kato mandata which is intended for the big fellow and kato malereng which is used for urang sumando.